Contingencies of Growth in Teaching Career in Nepal - Dhobi, Saleem (Patan Prospective Journal, 2025)
This paper examines diverse career possibilities in Nepalese education system. Teaching as one of the most renowned and prestigious professions embodies diverse facets that can enrich the basket of opportunities for both growth and satisfaction. This paper explores numerous possibilities of career growth in teaching that has been narrowed to the teaching and learning in the classroom and the compensation paid to the teachers based on that limited engagement. The paper counters the argument that teaching does not endow employees to grow much as expected and seen in other professions including engineering and medicine which are also traditional professions like teaching in both contexts national and global. Confining to the classroom may be monotonous for the teachers. The paper has employed an exploratory approach to unveiling the possibilities of growth by diversifying teaching. The data used in the paper are secondary and based on the participant observation. The purpose of this article is to investigate into different possibilities of growth pertaining to education. A teacher who begins her or his career in an elementary school can hold high-profile positions by relentlessly serving in the education sector and consequently she or he can experience exponential growth in the financial aspect of their lives as well.